Electrophilic iodination: a gateway to high iodine compounds and energetic materials. Issue 35 (11th August 2016) - Chand, Deepak; He, Chunlin; Mitchell, Lauren A.; Parrish, Damon A.; Shreeve, Jean'ne M.
Abstract : Preparation of polyiodopyrazoles and subsequent highly oxygenated nitro compounds. Abstract : A large number of iodine atoms can be introduced into a single molecule in a one-pot reaction using trifluoroperacetic acid-mediated electrophilic iodination methodology. The scope of this reaction was investigated extensively using several pyrazole substrates which resulted in nine polyiodo pyrazole compounds with iodine content as high as 80%. This synthetic methodology was also utilized successfully for iodination of benzimidazoles. Tetraiodobenzimidazole was nitrated with 100% nitric acid to give a high yield of 4, 5, 6, 7-tetranitro-1 H -benzimidazol-2(3 H )-one (14 ). All of these materials were fully characterized and compounds5, 9, 10 and14 were confirmed further with single crystal X-ray analysis. High density, positive oxygen balance, and very good impact sensitivity values characterize14 . For the first time, two 1, 2, 5-oxadiazole- N -oxide rings were introduced into a benzimidazole ring (11 ) which remarkably improves the stability of oxadiazole- N -oxide compounds.